Evaluation of The Integrated Protocol for The Management of Severe Malnutrition in Children at The National Hospital of Nouakchott-Mauritania - Sima Boulebatt Mahfoud; Hamid El Oirdi; El Hafedh El Mouhab; Nasser Abdellahi; Feil Ahmed; Jaouad Mostafi; Manal Maaroufi; Saïd Lotfi; Khadija El Kharrim; Driss Belghyti (Journal of Multidisciplinary Applied Natural Science, 2024)
Malnutrition is a worldwide concern with worrisome outcomes that affect substantially the lifestyle of infants. The main aim is to investigate the efficacy of the IMSAM protocol over malnourished Mauritanian children during hospitalization. A cohort of 230 participants, including 126 boys and 104 girls collected from rural and urban areas with an average age of 15.52 ± 7.727 months were enrolled. The study is carried out in the Pediatric Service of the National Hospital Center of Nouakchott, Mauritania on children who have undergone the national protocol for the Integrated Management of Severe Acute Malnutrition (IMSAM). In addition, the medical and nutritional treatment, and body measurements were appreciated as well as the anthropometric parameters. The findings exhibit during nutritional-based intervention significant differences between the mean of weight during the pre- and post-intervention (P < 0.001). Moreover, through a regression test, we found a negatively predicted weight gain (P < 0.05) by the variables Z-score of weight to height (P / T) Edema after Nutritional Support and final health status. Last, but by no means least, the IMSAM-based intervention with rational management might make inroads into mitigating adverse outcomes of malnutrition through maximizing social skills.